The use of controlled medications during the Covid-19 pandemic observed in a drugstore in the southwestern region of Bahia (Research, Society and Development, 2021)
The pandemic period and the protective measures, especially social distancing, may have caused impacts on the mental health of the population. Thus, the research sought to analyze how the use of controlled medications during the Covid-19 pandemic occurred, based on a drugstore located in a city in southwestern Bahia. The objective was to analyze this use through prescriptions, in order to identify the main pharmacological groups as well as the profile of the medications and their relations with the pandemic scenario. This is a retrospective longitudinal study, being a case-control of basic character. As a data source, we used medical prescriptions referring to Ordinance No. 344/98, seen at the drugstore during the months from March 2020 to March 2021, totaling 334 prescribed medications. The approach adopted for data analysis was qualitative and descriptive quantitative. The results indicated an increase in prescriptions in the month of May/2020, with a peak in the month of July, presenting small oscillations in the subsequent months until November. In December there was a decline, being high in the subsequent months. The most common groups were Selective Serotonin Reuptake Inhibitor Antidepressants (32.9%), most notably Fluoxetine (7.8%); Benzodiazepines (24.5%) with Clonazepam (13.8%); and Tricyclic Antidepressants (18.0%), Amitriptyline (15.3%). In a panoramic analysis, more in-depth studies are able to accurately identify the national scenario and allied to educational measures that guide the use and rational prescription of medicines in Brazil can reduce inappropriate use and avoid damage to health in the country.